Teacher Strategies in Developing Early Childhood Speaking Skills A Qualitative Study - Sari, Devi Rahmawati Purnama; Chasanatun, Fida; Susari, Hermawati Dwi (Kiddie: Early Childhood Education and Care Journal, 2026)
This study aims to analyze teacher strategies for fostering the speaking skills of 5–6-year-old children and to explore factors that support and constrain their implementation. A qualitative descriptive design was used. Participants consisted of the school principal and two Group B teachers who were directly involved in learning activities with 20 children. Data were collected through participatory observation, structured interviews, and documentation of learning plans and classroom activities. Data were analyzed through data condensation, data display, and conclusion drawing and verification. Credibility was strengthened through technique triangulation by comparing interview, observation, and documentation evidence. The findings indicate four interrelated themes: planned learning preparation, interactive and child-centred implementation, supporting and constraining factors, and continuous observation-based evaluation. Teachers combined conversation, open-ended questioning, storytelling, singing, role play, picture-based books, visual media, and positive feedback to create opportunities for children to speak. Children were observed to participate more actively in the speaking activities, while some still needed individualized support. The findings suggest that the contribution of teacher strategy lies not simply in the variety of methods, but in how teachers create meaningful opportunities for children to produce language, respond to children’s utterances, and adapt activities to individual needs.